Geological and geotechnical constraints in the Irish Sea for offshore renewable energy. Issue 2 (9th December 2020) - Coughlan, Mark; Long, Mike; Doherty, Paul
ABSTRACT: A 1:1, 000, 000 map of the Irish Sea, within the Irish Economic Exclusion Zone, is presented highlighting the spatial distribution of potential geological and geotechnical constraints to offshore wind energy development. In this mapping exercise we incorporated existing multibeam echosounder bathymetric and backscatter data collected by the Integrated Mapping for the Sustainable Development of Ireland's Marine Resource programme. ArcGIS was used to interrogate the bathymetric data and produce maps for seabed morphological characteristics. Backscatter data and QTC Multiview derived sediment classification was used in conjunction with data from the literature to link sediment distribution with sediment transport pathways and to assess the possible impact on infrastructure. The result is a spatial constraints map, which may be used by developers, consultants and marine spatial planning authorities alike to help site projects and plan de-risking site investigations.